DESIGN OF BORED PILE FOUNDATIONS AND PRELOADING ON AIRSIDE FACILITIES OF H.A.S. HANANDJOEDDIN AIRPORT TANJUNG PANDAN - Gangsar Gumilang, Angger
Belitung Island as a huge tourist attraction which results in an increase in the movement of tourists. To accommodate the increased movement, H.A.S. Hanandjoedin airport will be built. H,A.S. Hanandjoedin Airport is planned with airside facilities and a passenger terminal. The purpose of this thesis is to design the passenger terminal dfoundation and preloading on airside facilities. The design of the passenger terminal foundation and air facility preloading refers to SNI 8460: 2017. The foundation design is designed to resist and transfer loads on the superstructure. Bearing capacity and settlement are design criteria in foundation design. The types of soil in the airside facilities of H.A.S. Hanadjoedin Airport is dominated by clay soil at each layer. Preloading is used to overcome the settlement due to the structure on it. Preloading is done by applying embankment loads to the soils. Embankment leads to soil settlement. The relatively long process of soil settlement requires Prefabricated Vertical Drain to increase the speed of settlement. Preloading with support of Prefabricated Vertical Drain considers the bearing capacity of the soil and the coefficient of vertical consolidation. Results of the foundation design are diameter of the pile foundation, depth of the pile foundation, configuration of the pile and dimensions of the pile cap. Results of preloading design with PVD are embankment height, pattern and distance of Prefabricated Vertical Drain.